2013
DOI: 10.4149/bll_2012_132
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute swimming exercise on plasma leptin in rats

Abstract: Abstract:Exercise is known to increase free fatty acid and glucose metabolism. In consideration of such physiological effects of leptin such as reducing food intake and increasing energy consumption, many researchers have studied the relation between leptin and exercise. Despite the inconsistency between results, it is generally accepted that physical activity causes changes in leptin secretion. The present study aims to determine the changes that occur in plasma leptin levels of the rats subjected to acute sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This is supported by a study by Pagano et al (1999) that reported a strong relationship between swimming exercise and circulating leptin, in which plasma leptin was decreased by up to 30 % following exercise in normal rats. Many other animal studies (Baltaci et al 2012) as well as reports on swimmers and marathoners (Karamouzis et al 2002, Zaccaria et al 2002 have noted reduced plasma leptin levels immediately after exercise. However, there are some studies that found either increased concentrations (Flores et al 2006, Zareian et al 2011 or no changes in plasma leptin levels after exercise (Borg et al 2014).…”
Section: Vol 65mentioning
confidence: 87%
See 1 more Smart Citation
“…This is supported by a study by Pagano et al (1999) that reported a strong relationship between swimming exercise and circulating leptin, in which plasma leptin was decreased by up to 30 % following exercise in normal rats. Many other animal studies (Baltaci et al 2012) as well as reports on swimmers and marathoners (Karamouzis et al 2002, Zaccaria et al 2002 have noted reduced plasma leptin levels immediately after exercise. However, there are some studies that found either increased concentrations (Flores et al 2006, Zareian et al 2011 or no changes in plasma leptin levels after exercise (Borg et al 2014).…”
Section: Vol 65mentioning
confidence: 87%
“…Recent studies have demonstrated a connection between the HPA axis and adipose tissue (Hernandez et al 2000, Pralong andGaillard 2001). There is also evidence that several peripheral metabolic markers, such as leptin and ghrelin, are altered by stressful events such as maternal separation (Salzmann et al 2004, Schmidt et al 2006 as well as physical stress (Baltaci et al 2012, Zareian et al 2011. However, the effects of physical and social stress on stress and metabolic hormones are extremely variable.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the different responses seen in myokines due to exercise, these differences are also observed in relation to adipokines. In this regard, exercise appears to be an effective intervention for decreasing leptin, with many studies reporting a decrease in leptin after acute exercise [ 215 – 221 , 205 ]. In general, these studies showed that high-intensity exercises of 70–95% VO 2 max and resistance exercises with an intensity of 60–80% 1RM (3 sets of 12 repetitions) can be effective in decreasing leptin by 12–26% [ 215 – 221 ].…”
Section: Acute and Chronic Exercise Effects On Exerkinesmentioning
confidence: 99%
“…In this regard, exercise appears to be an effective intervention for decreasing leptin, with many studies reporting a decrease in leptin after acute exercise [ 215 – 221 , 205 ]. In general, these studies showed that high-intensity exercises of 70–95% VO 2 max and resistance exercises with an intensity of 60–80% 1RM (3 sets of 12 repetitions) can be effective in decreasing leptin by 12–26% [ 215 – 221 ]. Leptin levels seem to decrease after acute exercise for up to 12 h and in some studies for up to 24 h [ 215 – 221 ].…”
Section: Acute and Chronic Exercise Effects On Exerkinesmentioning
confidence: 99%
“…The changes in leptin levels may depend upon either exercise intensity/ duration or body mass changes [ 59 , 62 ]. Decreased leptin levels corresponded to decreased adiposity after exercise training, however leptin levels have also been shown to fall in response to acute exercise independent of changes in adiposity [ 11 , 151 , 208 ]. In any case, a decrease in leptin would not be in agreement with the activity profile exhibited by either POMC or NPY/AgRP neurons after exercise [ 97 ].…”
Section: Exercise Training Exerts Complex Adaptive Responses In the Amentioning
confidence: 99%